2024
DOI: 10.3390/ijms25020687
|View full text |Cite
|
Sign up to set email alerts
|

5-HT2A Receptor Knockout Mice Show Sex-Dependent Differences following Acute Noribogaine Administration

Sofía Villalba,
Bruno González,
Stephanie Junge
et al.

Abstract: Noribogaine (noribo) is the primary metabolite from ibogaine, an atypical psychedelic alkaloid isolated from the root bark of the African shrub Tabernanthe iboga. The main objective of this study was to test the hypothesis that molecular, electrophysiological, and behavioral responses of noribo are mediated by the 5-HT2A receptor (5-HT2AR) in mice. In that regard, we used male and female, 5-HT2AR knockout (KO) and wild type (WT) mice injected with a single noribo dose (10 or 40 mg/kg; i.p.). After 30 min., loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Furthermore, female sex is among the additional risk factors for drug-induced TdP arrhythmias that should be considered before the use of ibogaine [ 6 ]. Previous results have shown that the bioavailability of ibogaine and its principal in vivo metabolite, noribogaine, is two to three times higher in female rats than in male rats [ 9 , 10 ] and that ibogaine has sex-specific effects on the central nervous system [ 11 , 12 , 13 ], liver, and kidneys, with ibogaine-induced pathological changes being more pronounced in female rats [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, female sex is among the additional risk factors for drug-induced TdP arrhythmias that should be considered before the use of ibogaine [ 6 ]. Previous results have shown that the bioavailability of ibogaine and its principal in vivo metabolite, noribogaine, is two to three times higher in female rats than in male rats [ 9 , 10 ] and that ibogaine has sex-specific effects on the central nervous system [ 11 , 12 , 13 ], liver, and kidneys, with ibogaine-induced pathological changes being more pronounced in female rats [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%